Clinical outcomes of Najuta thoracic stent graft system for arch aneurysms - Iida, Yasunori; Hachiya, Takashi; Oka, Hidetoshi; Inaba, Yu; Miki, Takahisa; Shimizu, Hideyuki (Frontiers in Surgery, 2023)
Objectives: We elucidated the perioperative and midterm clinical outcomes of the Najuta thoracic stent graft system containing fenestration for supra-aortic vessels. Methods: From May 2019 to February 2023, we treated 20 patients with arch or distal arch aneurysms using the Najuta thoracic stent graft system. Herein, we retrospectively investigated the intraoperative and perioperative clinical outcomes with short-term follow-up. Results: The technical success rate was 95%. We performed concomitant extra-anatomical supra-aortic bypass in 17 patients (85.0%). Postoperative CT revealed type Ia (n = 2) and type II (n = 3) endoleaks which disappeared on follow-up. Postoperative complications were stroke (n = 2, 10.0%), paraplegia (n = 1, 5.0%), and paraparesis (n = 1, 5.0%). Blood transfusion was performed in a very old patient whose access route was taken from the common iliac artery by retroperitoneal approach. Aorta-related complications such as retrograde type A dissection or distal stent graft induced new entry were not observed. Conclusions: Perioperative and short-term clinical outcomes of the Najuta thoracic stent graft system were acceptable. We treated arch or distal arch thoracic aneurysms by inserting a tube-type stent graft as scaffold on the peripheral site and placing the Najuta stent graft on the proximal site. By extending the landing zone to Zone 0 and using a low radial force, which is a feature of the Najuta thoracic stent graft system, we avoided postoperative bird-beak and aorta-related complications. TEVAR with the Najuta thoracic stent graft system may become a treatment option for arch and distal arch aortic aneurysms.